PENGEMBANGAN COMPACT DISK (CD) INTERAKTIF MENGGUNAKAN MACROMEDIA FLASH PADA MATERI GEOMETRI UNTUK SISWA KELAS X SMAN 13 PADANG - Nurzal, Farid - (STKIP PGRI Sumbar, 2014)
This research is motivated by the students have difficulty in understanding theconcept of learning material. Therefore, the teacher should use the teaching aims inteaching learning process that can be guidance the student to study alone and it can makethe student become easy in understanding the concepts of learning material. Media whichcan be used such as interactive CD that is developed by using application macromediaflash. This research aims to know the validity and practicality interactive CD that usedmacromedia flash in Geometry material. The kind of this research is developing researchthat used 4-D model which consists of 4 steps to define, design, develop and disseminatethat explaine. In this research, the steps of the research is limited until develop model, thatconsist of validity and practicality. In short, the researcher concluded that interactive CDthat used macromedia flash in Geometry material in teaching math at SMAN 13 grade XPadang is categorized valid and practice.